1992
DOI: 10.1542/peds.89.6.1151
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health and Lung Function in 8-Year-Old Children of Very Low Birth Weight: A Cohort Study

Abstract: In comparison with a cohort of normal birth weight children, those of very low birth weight (<1501 g birth weight) had more wheezing illnesses and hospital readmissions for respiratory problems in the first 2 years of life; from 2 years to 8 years of age respiratory health was unrelated to birth weight. Lung function measurements at 8 years of age in very low birth weight children were similar to expected values; few children had severely abnormal lung function. On univariate analyses, forced vital capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Although premature birth may lead to alterations in pulmonary development after the neonatal period, 30 previous studies employing spirometry to evaluate subjects with a history of preterm birth have not demonstrated changes in lung function throughout childhood and adolescence, 31 , 32 as was found in the present study. However, in studies evaluating children and adolescents who were born preterm and who had a more severe history, spirometry has shown differences between such subjects and control subjects who were born at term.…”
Section: Discussionsupporting
confidence: 60%
“…Although premature birth may lead to alterations in pulmonary development after the neonatal period, 30 previous studies employing spirometry to evaluate subjects with a history of preterm birth have not demonstrated changes in lung function throughout childhood and adolescence, 31 , 32 as was found in the present study. However, in studies evaluating children and adolescents who were born preterm and who had a more severe history, spirometry has shown differences between such subjects and control subjects who were born at term.…”
Section: Discussionsupporting
confidence: 60%
“…Although the responses to the questionnaire must be interpreted with caution, the differences in lung function related to HMD found in this study do not appear to be clinically correlated. In various previous studies, prematurity has been related to airway obstruction and hyperresponsiveness, from infancy to adolescence [8,9,[15][16][17], and with clinical manifestations of respiratory disease, including asthma [18][19][20]. GALDES-SEBALDT et al [16] have suggested that prematurity is a greater determinant of later lung function than neonatal respiratory disease.…”
Section: Discussionmentioning
confidence: 97%
“…Lung function was mainly related to birth weight, although the smaller expiratory flows corresponded to the premature children who received treatment for neonatal respiratory disease. KITCHEN et al [8], in a cohort study, found that birth weight is directly related to FEV1 at 8 yrs of age, while at this age a history of BPD is only significantly associated with a greater residual volume. This relevant study supports the effect of prematurity on later lung function but does not exclude an independent effect of the neonatal respiratory disease and treatment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations